The empowered patient how to get the right diagnosis, buy the cheapest drugs, beat your insurance company, and get the best medical care every time - Cohen, Elizabeth 1935- (Ballantine Books Trade Paperbacks, 2010)
"Combining the personal stories of patients across America with crucial advice on receiving the best possible health care, this guide will enable you to confront and often confusing and perilous system--and come out ahead" --Cover, p. 4.